A New Historic ERS Wave Mode Data Set for Oceanographic Applications - König, Thomas; Lehner, Susanne; Schulz-Stellenfleth, Johannes; Schättler, Birgit (IEEE, 2004)
Since 1991, the ERS satellites have collected high resolution SAR data over the oceans on a global and continuous basis. Operating in wave mode the ERS SAR yields a patchy coverage of the oceans with about 1500 images of 10 by 5 km size each day. These data have recently been shown to be able to deliver wind speed and wave spectra as well as information on individual waves. In the scope of the ESA AO WaveAtlas, the ERS-2 raw data acquired in 1999 and 2000 are reprocessed to single look complex imagettes. This paper describes the necessary steps for the reprocessing of historic wave mode data including an assessment of the effort required to reprocess all available ERS wave mode raw data archived at ESA. Furthermore the paper demonstrates the potential of these data for different oceanographic applications. Special emphasize is put on wind, wave and sea ice measurements. In addition atmospheric features can be analyzed. The data in particular enable the estimation of two-dimensional sea surface elevation fields which are of high practical relevance for ship design or offshore operations. Mean wave parameters like the mean period derived from SAR wave mode data can be used for the assimilation of numerical wave models thus helping to improve wave forecast. Global maps of mean and individual wave parameters will be presented. The reprocessing of wave mode data is planned to be extended to the full lifetime of ERS-1 and ERS-2, which is at least 1991-2004. This will allow the derivation of wave climatologies on a decadal basis in particular enabling the analysis of climate trends. As wave mode data are also available from the ENVISAT mission a consistent update of these climatologies is possible